2016
DOI: 10.3349/ymj.2016.57.1.254
|View full text |Cite
|
Sign up to set email alerts
|

Initial Serum Ammonia as a Predictor of Neurologic Complications in Patients with Acute Glufosinate Poisoning

Abstract: PurposeGlufosinate poisoning can cause neurologic complications that may be difficult to treat due to delayed manifestation. Studies assessing possible predictors of complications are lacking. Although serum ammonia level is a potential predictor of severe neurotoxicity, it has only been assessed via case reports. Therefore, we investigated factors that predict neurologic complications in acute glufosinate-poisoned patients.Materials and MethodsWe conducted a retrospective review of 45 consecutive glufosinate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
(22 reference statements)
0
21
1
Order By: Relevance
“…3 Although glufosinate ammonium herbicides are considered safe when used properly, 4 many clinical toxicologists have reported that the ingestion of a large amount of glufosinate ammonium can cause convulsions. 5 –8…”
Section: Introductionmentioning
confidence: 99%
“…3 Although glufosinate ammonium herbicides are considered safe when used properly, 4 many clinical toxicologists have reported that the ingestion of a large amount of glufosinate ammonium can cause convulsions. 5 –8…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 72.0% of the patients were placed in the neurologic complication group. Some differences in the incidence of neurologic complications in previous studies exist 3,5,12,13 that may have occurred due to the definition of complication group and the severity of poisoned patients. However, similarities in the results of recent human studies (including our prospective study) indicate that acute glufosinate ammonium poisoning causes serious complications much more often than previously reported.…”
Section: Discussionmentioning
confidence: 89%
“…All patients with hyperammonemia upon ED arrival received a lactulose enema to lower the ammonia level, as high levels have been suggested to cause neurologic complications. 12 All glufosinate ammonium–poisoned patients were admitted to the intensive care unit (ICU) for close observation for more than 1 day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%